Neonatal Exposure to Endocrine Disrupting Chemicals Impairs Learning Behaviour by Disrupting Hippocampal Organization in Male Swiss Albino Mice. Issue 1 (15th March 2017) - Bhaskar, Rakesh; Mishra, Ashish K.; Mohanty, Banalata
Abstract: Hippocampus is highly susceptible to endocrine disrupting chemicals exposure particularly during the critical phase of brain development. In this study, mice offspring were exposed to endocrine disruptors mancozeb (MCZ) and imidacloprid (IMI) individually (40 mg MCZ and 0.65 mg IMI/kg/day) as well as to their equimixture (40 mg MCZ + 0.65 mg IMI/kg/day) through the diet of lactating mothers from post‐natal day (PND) 1 to PND 28. Half of the randomly selected male offspring were killed at PND 29, and the rest half were left unexposed and killed at PND 63. Brain weight, histology, plasma hormone profile and working memory performance were the various end‐points studied. Brain weight was significantly decreased in the mixture‐exposed group at PND 29, which persisted to PND 63. Total thickness of pyramidal cell layers decreased significantly along with misalignment, shrinkage and degeneration of pyramidal neurons in CA1 and CA3 regions of the IMI and mixture‐exposed groups. The length and branch points of dendrites of pyramidal neurons were decreased significantly in mixture‐exposed group at both PND 29 and PND 63. Dendritic spine density was also reduced in mixture‐exposed group offspring. Testosterone level was significantly decreased only at PND 29, but corticosterone level was increased at both PND 29 and PND 63 in mixture‐exposed offspring. T‐maze task performance revealed significantly increased time duration and reduced path efficiency in mixture‐exposed group offspring. The results thus indicate that pesticide mixture exposure could lead to changes in learning behaviour even at doses that individually did not induce any adverse effect on hippocampal organization.